2018
DOI: 10.3390/ijms19071846
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Stem Cell-Derived, Scaffold-Free Constructs for Bone Regeneration

Abstract: In the present study, a scaffold-free tissue construct was developed as an approach for the regeneration of tissue defects, which produced good outcomes. We fabricated a scaffold-free tissue construct from human dental pulp stem cells (hDPSCs construct), and examined the characteristics of the construct. For its fabrication, basal sheets prepared by 4-week hDPSCs culturing were subjected to 1-week three-dimensional culture, with or without osteogenic induction, whereas hDPSC sheets (control) were fabricated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
3
14
0
4
Order By: Relevance
“…At 21 days of culture, they observed structures of the extracellular matrix consistent with collagen fibers. Spherical structures were associated with vesicles of the matrix because they had a diameter of 40 to 200 nm and because these have been considered to play a fundamental role in the process of bone calcification ( Arahira and Todo, 2014 ; Tatsuhiro et al., 2018 ). Besides, the presence of HA crystals in the scaffold offers suitable mechanical proprieties, and roughness which can increase cell adhesion ( Geckil et al., 2010 ; Lou et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…At 21 days of culture, they observed structures of the extracellular matrix consistent with collagen fibers. Spherical structures were associated with vesicles of the matrix because they had a diameter of 40 to 200 nm and because these have been considered to play a fundamental role in the process of bone calcification ( Arahira and Todo, 2014 ; Tatsuhiro et al., 2018 ). Besides, the presence of HA crystals in the scaffold offers suitable mechanical proprieties, and roughness which can increase cell adhesion ( Geckil et al., 2010 ; Lou et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…[37] Further decellularization allows either the reseeding of the CDMs in patients or with other cell types, or to use them acellularly for applications in regenerative medicine. [38,39] The previously described decellularization approaches can be used to produce several micrometer thick sheets of ECM mimicking native tissue properties based on the cell source. [40] Prewitz et al demonstrated that mesenchymal stem cell (MSC)derived ECM coatings can act as an ex vivo niche for human hematopoietic stem cell (hHSC) expansion, generating up to a threefold increase in the number of cells compared to conventional plasma-treated tissue culture plates.…”
Section: D Surfaces To Produce Cell Sheetsmentioning
confidence: 99%
“…A study compared the osteogenic potential of the cell sheet and the bone construct from DPSCs and showed that the cell construct was more effective in inducing oral bone formation. In vitro, the differentiated construct showed the highest expression of bone biomarkers at the mRNA and protein level—osteopontin (OPN), bone sialoprotein (BSP), osteocalcin (OCN) and type I collagen (Col 1)—when compared to the sheet or to the undifferentiated cells [89].…”
Section: Stem Cells-based Scaffold-free Bone Regenerationmentioning
confidence: 99%